PROPOSED STRATEGY OF MRO OPTIMIZATION IN COST-EFFECTIVE PROGRAM BY USING KEPNER-TREGOE ANALYSIS AND ANALYTICAL HIERARCHY PROCESS (AHP) - Ariawan, Yona; Yudoko, Gatot (JEMIS (Journal of Engineering & Management in Industrial System), 2023)
ADC Company is a global company which operates in the Middle East that has been running to supply the downstream users with its product such as Ethylene, Polyethylene and Polypropylene. The current performance and objectives show that we need to take a look at something that can be done possibly and take the initiative that can be improving the company’s performance, especially in this kind of situation. The current setup of Maintenance Repair and Operations or MRO of this company, has shown the value that this company has 43% Non-Moving Spare Part (PNM-SP) Material value that is excessive and has turned into a particular issue for the Company. However, there is an opportunity for the company to make more effective inventory through the inventory policy strategy and improvement. The higher the inventory value and the remaining items/materials that cannot be utilized, then the worse the inventory performance reflects. Therefore, the business problem could be identified and further transformed into a problem statement as Significant Potential Non-Moving Spare Part (PNM-SP) Materials all across the years have resulted in the inefficiency of Operational Expenditures (OPEX) which costs the company with unused/ never used bought materials associated with handling and maintaining cost produced by those (PNM-SP) materials. The objectives of this research are overcome or reduce the volume of Potential Non-Moving Spare parts (PNM-SP) Materials in our organization, and What tactics or alternative solutions exist to avoid massive Potential Non-Moving Spare parts (PNM-SP) Materials, along with the precautions that should be taken in the event happens in the future, by using Kepner Tregoe Analysis and Analytical Hierarchy Process (AHP). In this scenario, we will be utilizing some feedbacks from our references along with their major result.